2008
DOI: 10.1111/j.1365-294x.2008.04005.x
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the history of speciation in house mice from autosomal, X‐linked, Y‐linked and mitochondrial genes

Abstract: Patterns of genetic differentiation among taxa at early stages of divergence provide an opportunity to make inferences about the history of speciation. Here, we conduct a survey of DNA-sequence polymorphism and divergence at loci on the autosomes, X chromosome, Y chromosome and mitochondrial DNA in samples of Mus domesticus, M. musculus and M. castaneus. We analyzed our data under a divergence with gene flow model and estimate that the effective population size of M. castaneus is 200 000–400 000, of M. domesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

52
313
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 235 publications
(369 citation statements)
references
References 86 publications
52
313
4
Order By: Relevance
“…This result agrees with increasing evidence of a southeast Asian lineage within MUS, as well as current views of the geographic origin of the MUS genomic contribution to MOL (Yonekawa et al, 2012). NOR variability levels are in agreement with colonization patterns that predict higher diversity in populations from the area of origin compared with those present in peripheral regions (Geraldes et al, 2008;Rajabi-Maham et al, 2008). Thus, CAS from the Indo-Pakistani region has the highest mean heterozygosity value among the subspecies (Table 1), although MOL is the one that shows the highest diversity in number of NOR-bearing chromosomes (13 vs 11 in the other subspecies).…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…This result agrees with increasing evidence of a southeast Asian lineage within MUS, as well as current views of the geographic origin of the MUS genomic contribution to MOL (Yonekawa et al, 2012). NOR variability levels are in agreement with colonization patterns that predict higher diversity in populations from the area of origin compared with those present in peripheral regions (Geraldes et al, 2008;Rajabi-Maham et al, 2008). Thus, CAS from the Indo-Pakistani region has the highest mean heterozygosity value among the subspecies (Table 1), although MOL is the one that shows the highest diversity in number of NOR-bearing chromosomes (13 vs 11 in the other subspecies).…”
Section: Discussionsupporting
confidence: 78%
“…The NOR-based phylogeny is essentially compatible with the currently established relationships for the three main subspecies: DOM is the most differentiated subspecies whereas MUS and CAS are more closely related (Bonhomme et al, 2007), although all sister group associations have been found depending on the marker used (see Bonhomme et al, 2007;Geraldes et al, 2008). MOL, which carries a MUS/CAS composite genome has, as expected, an intermediate position in the tree.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations